Unification of Two-Variable Family of Apostol-Type Polynomials with Applications - Beih S. El-Desouky; Rabab S. Gomaa; Alia M. Magar (Journal of Mathematics)
In this paper, the two-variable unified family of generalized Apostol-type polynomials is introduced, and some implicit forms and general symmetry identities are derived. Also, we obtain new degenerate Apostol-type numbers and polynomials constructed from the new 2-variable unified family. We derive explicit formulae of polynomials and identities that include some special numbers and polynomials. In addition, a probabilistic representation of the new family and some statistical properties are obtained.